Early increase in circulating carbonic anhydrase IX: A potential new predictive biomarker of preeclampsia - Galbiati, Silvia; Gabellini, Daniela; Ambrosi, Alessandro; Soriani, Nadia; Pasi, Federica; Locatelli, Massimo; Lucianò, Roberta; Candiani, Massimo; Valsecchi, Luca; Zerbini, Gianpaolo; Smid, Maddalena (Frontiers in Molecular Biosciences, 2023)
Preeclampsia (PE) is a severe complication of pregnancy. The identification of a reliable predic-tive biomarker could help setting up a specific preventive strategy. To this aim, we studied CAIX as a marker of hypoxia (pathway involved in PE pathogenesis) and compared the diagnos-tic accuracy of CAIX to the one of validated biomarker sFlt1/PlGF ratio. Fifteen women with overt PE and 38 women at risk of developing PE, sampled at different time intervals during ges-tation (for a total of 82 plasma samples collected), were enrolled and underwent CAIX meas-urement. CAIX levels were significantly increased (p<0.001) before the onset of the disease in women (25% of total number) that later on developed PE when compared to women who did not starting from 28th gestational week. The best CAIX cut-off of 68.268 pg/mL yielded a sensitiv-ity of 100%, a specificity of 81.82% and an AUC= 0.9221. In our pilot study when compared to sFlt1/PlGF ratio, CAIX performed better in predicting PE before clinical onset. Furthermore when implemented as CAIX/PlGF ratio, showed up to be comparable in the identification of women with overt early PE. In conclusion, CAIX could represent an effective predictive biomarker of PE, larger studies are mandatory to validate this finding.